Fixed-Time Adaptive Distributed Fault-Tolerant Cooperative Control for Multiple Quad-rotors - Xu, Hui; Cui, Guozeng (2023 6th International Symposium on Autonomous Systems (ISAS), 2023)
This paper explores a fixed-time adaptive distributed fault-tolerant cooperative control strategy for multiple quadrotors subject to actuator faults. The explosion of complexity phenomenon is removed in a fixed time by the command filter. To surmount the filtering error influence, the fixed-time error compensation signals are constructed. Furthermore, the singularity problem is subtly avoided via a smooth piecewise function. It is proved that all closed-loop signals are bounded in a fixed time and that the cooperative tracking errors fixed-time converge to the neighboring range of the origin. A simulation example reveals the validity of the developed fixed-time distributed fault-tolerant cooperative control algorithm.